2007
DOI: 10.1152/ajpcell.00552.2006
|View full text |Cite
|
Sign up to set email alerts
|

Actin-dependent regulation of connective tissue growth factor

Abstract: Expression of connective tissue growth factor (CTGF) in endothelial cells is modulated by shear stress affecting the organization of the cytoskeleton. The molecular connection between alterations of actin and CTGF expression was investigated in human umbilical vein endothelial cells (HUVEC) and a microvascular endothelial cell line. Overexpression of nonpolymerizable monomeric actin R62D interfered with stress fiber formation in HUVEC and concomitantly reduced immunoreactive CTGF. In microvascular endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 32 publications
3
73
1
Order By: Relevance
“…The effects of CA-4P, the water-soluble form of CA-4, were analyzed in a mouse microvascular endothelial cell line (glEND.2), which has been used previously to characterize the relationship between alterations of the cytoskeleton and CTGF expression (23). Treatment with nanomolar concentrations of CA-4P led to a time-and concentration-dependent disruption of microtubular structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of CA-4P, the water-soluble form of CA-4, were analyzed in a mouse microvascular endothelial cell line (glEND.2), which has been used previously to characterize the relationship between alterations of the cytoskeleton and CTGF expression (23). Treatment with nanomolar concentrations of CA-4P led to a time-and concentration-dependent disruption of microtubular structures.…”
Section: Resultsmentioning
confidence: 99%
“…Nonuniform shear stress-induced upregulation of CTGF has been shown to involve activation of Rho proteins (22). In our previous study, G-actin was identified as negative regulator of CTGF expression downstream of RhoA activation, providing evidence for a direct link between alteration of the actin cytoskeleton and CTGF expression (23).…”
Section: Introductionmentioning
confidence: 88%
“…We therefore sought to determine whether the nuclear localization of MKL1/2 in DLC1-deficient hepatocellular and mammary carcinoma cells results in activation of its target genes. We first tested the expression of CTGF, which has been classified as an SRF-dependent target gene (Muehlich et al, 2007;Medjkane et al, 2009). CTGF also appeared in a recent microarray study by Medjkane et al as a MKL-dependent target gene (Medjkane et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…MKL1 expression was downregulated by 85% at protein and RNA levels ( Figure 5a). Two immediate early genes known to be SRF target genes (Selvaraj and Prywes, 2004;Miano et al, 2007;Muehlich et al, 2007), namely connective tissue growth factor (CTGF) and integrin alpha 5 (Itga5), showed preferential expression in HuH7 versus HepG2 cells, as well as MDA-MB-468 versus MCF7 cells (Figure 5b and Supplementary Figure S4). Both have been reported to have an important role in tumorigenesis (Friedl and Wolf, 2003;Mazzocca et al, 2010).…”
Section: Mkl1 Phosphorylation Status Contributes To Nuclear Localizatmentioning
confidence: 99%
“…Since T 4 is a potent pro-angiogenic factor 21 , an involvement of the T 4-MRTF-SRF axis in vascular growth would require transcriptional activation beyond well-known myogenic proteins 13,14 . However, MRTF coactivaton of SRF induces pro-angiogenic factors such as CCN1 (Cyr61) 22 and maturation factors such as connective tissue growth factor (CTGF) 23,24 . Moreover, SRF controls tip cell behaviour in angiogenesis 25,26 , indicating a role of MRTF-SRF in vascular growth and maintenance.…”
mentioning
confidence: 99%